Clinical Practice Guidelines for Vascular Catheter Infections Treatment. - Belkys Rodríguez Llerena; Marcos Diosdado Iraola Ferrer (Medisur)
Clinical Practice Guidelines for Vascular Catheter Infections Treatment. It has been defined as the presence of local or systemic signs without other obvious infection site, plus the microbiologic evidence involving the catheter. This document includes a review and update of concepts, main clinical aspects, and treatment and stresses the importance of prophylactic treatment. It includes assessment guidelines focused on the most important aspects to be accomplished.